Students’ basic psychological needs in blended teacher learning groups - De Vocht, Ann; Vrieling-Teunter, Emmy; Sins, Patrick; Vermeulen, Marjan (Frontiers in Education, 2023)
Introduction Student teachers (henceforth: students) in higher education often experience feelings of emotional loneliness that negatively impact upon their well-being and motivation to learn. Consequently, the importance of social learning for students has gained increased prominence, with Teacher Learning Groups (TLGs), that is, social configurations in which students, in-service teachers, and teacher educators, sometimes supplemented by researchers and/or experts, collaboratively learn through social interactions, being introduced in teacher training institutes. Ordinarily, TLGs organized their meetings face-to-face; however, due to COVID-19 measures, they had to rapidly transition to blended meetings, which in turn impacted upon students’ basic psychological needs. Methods In the present study, a convergent parallel mixed-methods design was utilized. The variables Social Configurations (Practice integration, Long-term orientation and goals; Shared identity and equal relationships) and Basic Psychological Needs (Competence, Autonomy, Relatedness) were assessed through the use of qualitative interviews and by administering two online quantitative surveys: the “Dimensions of Social Learning Questionnaire” and the “Basic Psychological Need Satisfaction and Frustration Scale”. Seventy students completed the questionnaires, while 14 students were interviewed. The students were recruited from four teacher training institutes. Results The analyses reveal that the more students perceive Shared identity and equal relationships in blended TLGs, the greater the fulfillment of Basic Psychological Needs they experience. Moreover, the more students experience the fulfillment of the need for Competence, the more students perceive TLGs’ Social Configurations. Discussion Based on the findings, we conclude that, although in-depth learning is more challenging during distance learning, blended TLGs are valuable for students’ Basic Psychological Needs during unpredictable times.